Supra-lacrimal protein-based carriers for cyclosporine A reduce Th17-mediated autoimmunity in murine model of Sjögren's syndrome. (April 2022) - Guo, Hao; Ju, Yaping; Choi, Minchang; Edman, Maria C.; Louie, Stan G.; Hamm-Alvarez, Sarah F.; MacKay, J. Andrew
Abstract: Sjögren's syndrome (SS) is a multifactorial autoimmune disease with principal symptoms including inflammation and loss of function of lacrimal glands (LG) and salivary glands. While glandular infiltrates includes both B- and T-cells, CD4 + T cells are strongly implicated. Utilizing the male non-obese diabetic (NOD) mouse model of SS, this work: 1) identifies clinically-relevant elevations in cytokines (IL-17A, IL-2) in LG-derived CD4 + T cells; and 2) explores tissue-specific immunosuppression of SS using a novel protein-based drug carrier to concentrate cyclosporine A (CsA) directly in the LG. As a potent immunosuppressant, topical ophthalmic CsA is approved for dry eye disorders; however, it cannot effectively resolve inflammation due to limited accumulation in the LG. Systemic CsA has dose-limiting side effects that also limit its ability to block LG inflammation. Using elastin-like polypeptides (ELPs) fused genetically to cyclophilin, the intracellular cognate receptor of CsA, this manuscript reports a sustained-release formulation of CsA that maintains therapeutic drug concentrations in the LG and extends intervals between doses. This formulation blocked both in vitro Th17 cell differentiation and IL-17A secretion. In vivo treatment significantly decreased the abundance of Th17.1 cells, a helper cell population sharing phenotypes of both Th17 and Th1, in the LG of diseased NOD mice. Treatment with even a single dose of the sustained-release formulation was effective enough to improve basal levels of tear production. Thus, this sustained-release formulation suppressed local LG inflammation driven through IL-17 dependent pathways, while improving ocular surface function.